Capacitance-dominated hierarchical porous three-dimensional carbon framework enhanced Prussian blue analogue as superior cathode for sodium-ion batteries. (5th June 2022) - Qi, Wentao; Jiang, Wen; Wang, Menglei; Ling, Rui; Yang, Chao; Wang, Yinghua; Cao, Bingqiang
Abstract: The 3D framework carbon is an ideal host of active materials for energy storage batteries. In this work, Kx Nay Mn[Fe(CN)6 ] (KNMF) nanocubes were in-situ grown on hierarchical porous 3D framework carbon (3DFC) to construct a composite cathode (KNMF@3DFC) for sodium-ion batteries. Owing to the hierarchical porous structure and large specific surface area, the highly conductive 3DFC offers abundant active sites for sodium storage and contributes to extra capacity. The considerable content of surface capacitance-dominated sodium storage of KNMF@3DFC composite cathode reveals faster charge transfer and better reaction kinetics, conducing to its rate capability. Ex-situ XRD/Raman measurements further reveal well structural stability of KNMF@3DFC during the whole cycle. Consequently, the KNMF@3DFC composite electrode reveals excellent rate performance and superior long-term cycling stability. Combining active materials with 3D framework carbon to enable a capacitance-dominated sodium storage mechanism is a promising strategy to stimulate the development of advanced electrode materials.